Pelatihan Keterampilan Komunikasi Interpersonal Santri Berbasis Nilai-Nilai Islam - Muhamad HanifFuadi; Frista FitrianyRamadhanita (Kusuma: Jurnal Pengabdian kepada Masyarakat, 2026)
This service activity aims to improve students' interpersonal communication skills through training based on Islamic values at the As-Sholeh Cipedes Islamic Boarding School, Tasikmalaya City. In the context of pesantren, effective communication skills are essential to form harmonious social relationships, strengthen morals, and build spirituality-based leadership. The method used is Participatory Action Research (PAR), which actively involves students in planning, implementing, and evaluating training programs. The training was held for four weeks with eight meeting sessions that combined modern communication techniques and Islamic principles such as qaulan karima and qaulan layyina. The results of the evaluation showed a significant increase in participants' interpersonal communication skills, both in terms of confidence in speaking, active listening, empathy, conflict resolution, and non-verbal communication, with an average increase of 26.4%. The participants' responses showed high enthusiasm, and most were able to internalize Islamic values into their daily communication practices. The follow-up three months after the program also showed the sustainability of positive impacts, including the emergence of students as communication mentors. This program has succeeded in creating a training model that is not only technical and applicative, but also ethically and spiritually transformative, strengthening the character of students as agents of social change based on Islamic values.